Tuberculosis Knowledge and Attitude of Patients in Community Health Center in Payakumbuh - Amelya Afryandes (HUMAN CARE JOURNAL, 2020)
Abstract Background. Tuberculosis (TB) remains an issue in Payakumbuh. A good knowledge and attitude have a crucial role towards TB control. The objective of this study was to assess knowledge and attitude related to TB among patients in Payakumbuh with structured questionnaire. Methods. Adult tuberculosis patients were selected randomly from eight community health centers in Payakumbuh during February to April 2018. Data were analysed using descriptive statistics. Result. A total of 32 patients were participated in this survey. From the finding, 68,75% respondents were male and 31,25 % were female. Of them 65% of respondents got information about TB from health care professional. Over 80% respondents have known that TB is a communicable disease. The fact that TB is caused by bacteria was known by 75% respondent. Surprisingly only 31,25% respondents who answered that smoking is not the cause of TB. All of respondents believed that TB is curable. Majority of the respondents 90,625% said that the proper medication from community health center is the best way to treat the disease. Conclusion. This study shows that patients had good attitude toward TB while improvement of knowledge is still needed.